Analisis Perbandingan Kinerja Web Server Apache dan Nginx Menggunakan Httperf Pada Portal Berita (Studi Kasus beritalinux.com) - Intan Ferina Irza; Zulhendra Zulhendra; Efrizon Efrizon (Universitas Negeri Padang, 2017)
The internet world in the globalization era is now developing. Anyone and anywhere can access the internet if you already have the tools and connections are adequate. There are two-ways relationship in accessing a web, they are Client and Server. Good Web Server performance can affect the quality of two-ways relationship between Client and Server. There are two Web Servers that are widely used today are Apache and Nginx. As a media content provider is expected to meet all the needs of users, especially in terms of performance of the device itself. To prove how the apache and nginx Web Server performance compare to the data request by the user, it is necessary to do a test and compare the parameters of each Web Server. Based on the problems above, the authors want to analyze and compare the performance of both Web servers are Apache and Nginx, so users can choose the best Web Server. The author only compares the parameters of throughput, connection, request, reply and error by assigning load to each test and performed on attributes that exist on beritalinux.com virtually. After testing, the results obtained where in responding and connecting data that requested by the client of web application server nginx was superior to apache. From these results, it is recommended to admin on beritalinux.com to use nginx web server for better website performance.Keywords: Analysis, Performance, Web Server, Apache, Nginx, HTTPERF